Respuesta :

Answer:

The solution is:

[tex]x=\frac{\sqrt{29}+7}{2},\:x=\frac{-\sqrt{29}+7}{2}[/tex]

Step-by-step explanation:

Given the equation

[tex]x^2\:-7x=\:-5[/tex]

[tex]\mathrm{Add\:}a^2=\left(-\frac{7}{2}\right)^2\mathrm{\:to\:both\:sides}[/tex]

[tex]x^2-7x+\left(-\frac{7}{2}\right)^2=-5+\left(-\frac{7}{2}\right)^2[/tex]

[tex]x^2-7x+\left(-\frac{7}{2}\right)^2=\frac{29}{4}[/tex]

Apply perfect square rule

[tex]\left(x-\frac{7}{2}\right)^2=\frac{29}{4}[/tex]

[tex]\mathrm{For\:}f^2\left(x\right)=a\mathrm{\:the\:solutions\:are\:}f\left(x\right)=\sqrt{a},\:-\sqrt{a}[/tex]

solving

[tex]x-\frac{7}{2}=\sqrt{\frac{29}{4}}[/tex]

[tex]x-\frac{7}{2}=\frac{\sqrt{29}}{\sqrt{4}}[/tex]

[tex]x-\frac{7}{2}=\frac{\sqrt{29}}{2}[/tex]

[tex]\mathrm{Add\:}\frac{7}{2}\mathrm{\:to\:both\:sides}[/tex]

[tex]x-\frac{7}{2}+\frac{7}{2}=\frac{\sqrt{29}}{2}+\frac{7}{2}[/tex]

[tex]x=\frac{\sqrt{29}+7}{2}[/tex]

also solving

[tex]x-\frac{7}{2}=-\sqrt{\frac{29}{4}}[/tex]

[tex]\mathrm{Add\:}\frac{7}{2}\mathrm{\:to\:both\:sides}[/tex]

[tex]x-\frac{7}{2}+\frac{7}{2}=-\frac{\sqrt{29}}{2}+\frac{7}{2}[/tex]

[tex]x=\frac{-\sqrt{29}+7}{2}[/tex]

Thus, the solution is:

[tex]x=\frac{\sqrt{29}+7}{2},\:x=\frac{-\sqrt{29}+7}{2}[/tex]